Development of a Digital-Based Character Diagnostic Assessment for the Pancasila Student Profile - Mauliza, Mauliza; Seprianto*, Seprianto; Oktaviani, Coryna; Nurhafidhah, Nurhafidhah; Yukwa, Bernard Alpha (Jurnal IPA & Pembelajaran IPA, 2025)
The main issue in implementing the merdeka curriculum in schools is the absence of valid, reliable, and digital-based diagnostic assessment instruments to specifically measure the character traits of the pancasila student profile, such as leadership and motivation. The aim of this research is to develop a digital-based character diagnostic assessment for the pancasila student profile that is feasible and can be implemented according to needs. This research uses research and development (RD) methods, with the 4-D development model (define, design, develop, and disseminate). Feasibility testing by experts showed that all the leadership and motivation diagnostic instrument items were feasible. The average validity of leadership and motivation diagnostic instruments according to experts is in the very high category with average Aiken's V values of 0.881 and 0.906, respectively. The reliability of the leadership diagnostic instrument according to experts is in the high category while the motivation diagnostic instrument is very high with cronbach's alpha values of 0.735 and 0.924 respectively. The validity of the leadership diagnostic instrument, large-scale test results show that almost all items are valid (13 out of 14 items) while the motivation diagnostic instrument shows that all items (30 items) are valid. Leadership and motivation instruments after large-scale test results show very high reliability with KR-20 reliability coefficient values of 0.95 and 0.91 respectively